KOMET: an unblinded, randomised, two parallel-group, stratified trial comparing the effectiveness of levetiracetam with controlled-release carbamazepine and extended-release sodium valproate as monotherapy in patients with newly diagnosed epilepsy. Issue 10 (29th August 2012) - Trinka, Eugen; Marson, Anthony G; Van Paesschen, Wim; Kälviäinen, Reetta; Marovac, Jacqueline; Duncan, Benjamin; Buyle, Sonja; Hallström, Yngve; Hon, Petr; Muscas, Gian Carlo; Newton, Mark; Meencke, Heinz-Joachim; et al.
Abstract : Objective: To compare the effectiveness of levetiracetam (LEV) with extended-release sodium valproate (VPA-ER) and controlled-release carbamazepine (CBZ-CR) as monotherapy in patients with newly diagnosed epilepsy. Methods: This unblinded, randomised, 52-week superiority trial (NCT00175903 ) recruited patients (≥16 years of age) with ≥2 unprovoked seizures in the previous 2 years and ≥1 in the previous 6 months. The physician chose VPA or CBZ as preferred standard treatment; each patient was randomised to standard treatment or LEV. The primary outcome was time to treatment withdrawal (LEV vs standard antiepileptic drugs (AEDs)). Analyses also compared LEV with VPA-ER, and LEV with CBZ-CR. Findings: 1688 patients (mean age 41 years; 44% female) were randomised to LEV (n=841) or standard AEDs (n=847). Time to treatment withdrawal was not significantly different between LEV and standard AEDs: HR (95% CI) 0.90 (0.74 to 1.08). Time to treatment withdrawal (HR (95% CI)) was 1.02 (0.74 to 1.41) for LEV/VPA-ER and 0.84 (0.66 to 1.07) for LEV/CBZ-CR. Time to first seizure (HR, 95% CI) was significantly longer for standard AEDs, 1.20 (1.03 to 1.39), being 1.19 (0.93 to 1.54) for LEV/VPA-ER and 1.20 (0.99 to 1.46) for LEV/CBZ-CR. Estimated 12-month seizure freedom rates from randomisation: 58.7% LEV versus 64.5% VPA-ER; 50.5% LEV versus 56.7% CBZ-CR. Similar proportions of patients within each stratum reported at least one adverse event: 66.1% LEV versus 62.0% VPA-ER; 73.4% LEV versus 72.5% CBZ-CR. Conclusions: LEV monotherapy was not superior to standard AEDs for the global outcome, namely time to treatment withdrawal, in patients with newly diagnosed focal or generalised seizures.